The hardness analysis of noodles made from modified cassava flour, spirulina (Spirulina platensis) and basil leaves extract (Ocimum sanctum L.). Issue 1 (February 2021) - Al-Baarri, A N; Widayat,; Aulia, R; Prahasiwi, E K; Mawarid, A A; Pangestika, W; Lestari, F P
Abstract: The alternative solution for high import costs of wheat flour is by substituting wheat flour with mocaf (modified cassava flour). Mocaf is a modification of cassava flour made by fermentation treatment using lactic acid bacteria, acetic acid or enzymes. However, mocaf has a low gluten and protein content so it might produce noodle products with a poor texture. Therefore, it is necessary to add other ingredients in order to increase protein content and change the appearance, one of which is fortification with spirulina. Spirulina has a natural aroma like the smell of fresh seaweed with a slightly fishy aroma that comes from the high protein content. Hence, it is necessary to add basil leaf extract which can give a distinctive smell of basil to overcome the fishy aroma of the noodles. This research was conducted to determine the texture of modified noodles from mocaf with the addition of spirulina and basil leaf extract using a texture analyzer. Based on the research conducted, it was found that the addition of basil and spirulina leaf extracts could affect the texture of mocaf noodles to become more chewy, dense and not easily broken.